Hypermobile Anterior Horn of the Lateral Meniscus: A Case Report and Literature Review. (23rd December 2020) - Nakashima, Hirotaka; Takahara, Yasuhiro; Uchida, Yoichiro; Kato, Hisayoshi; Itani, Satoru; Tsujimura, Yoshitaka; Nakamura, Makoto; Iwasaki, Yuichi
Abstract : Hypermobile meniscus is known as one of the causes of knee pain and locking or limitation of the range of motion during knee flexion, even when there is no evidence of meniscus tear on magnetic resonance imaging (MRI). Most such cases show excessive hypermobility of the posterior part of the lateral meniscus. This case report presented a rare case of a hypermobile anterior horn of the lateral meniscus. An 18-year-old woman visited our hospital for left knee pain without trauma. Her physical examination showed a limited range of motion and tenderness in the lateral joint space. However, her MRI did not show any abnormalities. After conservative treatment failed, we performed arthroscopic surgery. The arthroscopic evaluation showed no meniscus and no other intraarticular injury. However, the anterior horn of the lateral meniscus was easily translated beyond the lateral condyle by using a probe. Thus, hypermobile anterior horn of the lateral meniscus was diagnosed. The meniscus was stabilized by the outside-in technique. Immediately after surgery, the catching symptom and pain were alleviated. After three-and-a-half months, she returned to work. The Lysholm score improved from 55, preoperatively, to 100, 1-year postoperatively. In conclusion, careful arthroscopic evaluation is essential for the diagnosis of a hypermobile anterior horn of the lateral meniscus. Arthroscopic meniscus stabilization provides a good outcome for hypermobile meniscus.